White light-emitting electrochemical cells based on metal-free TADF emitters - Shi Tang; Youichi Tsuchiya; Jia Wang; Chihaya Adachi; Ludvig Edman (Nature Communications)
Abstract The attainment of white emission from a light-emitting electrochemical cell (LEC) is important, since it enables illumination and facile color conversion from devices that can be cost-efficient and sustainable. However, a drawback with current white LECs is that they either employ non-sustainable metals as an emitter constituent or are intrinsically efficiency limited by that the emitter only converts singlet excitons to photons. Organic compounds that emit by thermally activated delayed fluorescence (TADF) can address these issues since they can harvest all excitons for light emission while being metal free. Here, we report on the first white LEC based on solely metal-free TADF emitters, as accomplished through careful tuning of the energy-transfer processes and the electrochemically formed doping structure in the single-layer active material. The designed TADF-LEC emits angle-invariant white light (color rendering index = 88) with an external quantum efficiency of 2.1 % at a luminance of 350 cd/m2.